Obesity mediates the opposite association of education and diabetes in Chinese men and women: Results from the REACTION study. Issue 11 (11th October 2022) - Zhu, Yuanyue; Hu, Chunyan; Lin, Lin; Wang, Shuangyuan; Lin, Hong; Huo, Yanan; Wan, Qin; Qin, Yingfen; Hu, Ruying; Shi, Lixin; Su, Qing; Yu, Xuefeng; et al.
Abstract: Background: Evidence regarding the impact of education on diabetes risk is scarce in developing countries. We aimed to explore the association between education and diabetes within a large population in China and to identify the possible mediators between them. Methods: Information on educational level and lifestyle factors was collected through questionnaires. Diabetes was diagnosed from self‐report and biochemical measurements. A structural equation model was constructed to quantify the mediation effect of each mediator. Results: Compared with their least educated counterparts, men with college education had a higher risk of diabetes (odds ratio [OR] 1.19; 95% confidence interval [CI], 1.12–1.27), while college‐educated women were less likely to have diabetes (OR 0.77; 95% CI, 0.73–0.82). Obesity was the strongest mediator in both genders (proportion of mediation: 11.6% in men and 23.9% in women), and its association with education was positive in men (β[SE] 0.0387 [0.0037]) and negative in women (β[SE] −0.0824 [0.0030]). Taken together, all behavioral factors explained 12.4% of the excess risk of diabetes in men and 33.3% in women. Conclusions: In a general Chinese population, the association between education level and diabetes was positive in men but negative in women. Obesity was the major mediator underlying the education disparities of diabetes risk, with a stronger mediation effect among women. Abstract : Highlights The association between education level and diabetes in Chinese adults is positive in men but negative in women. Obesity is the major mediator underlying the gender disparity in the association between education and diabetes. Combating obesity may help address the burden of diabetes across education levels in both genders. 摘要: 目的: 在发展中国家，关于教育对糖尿病风险的影响的证据很少。我们的目的是在中国的一个大人群样本中探索教育和糖尿病之间的联系，并确定可能的中介因素。 材料和方法: 通过问卷调查，收集有关文化程度和生活方式因素的信息。糖尿病的诊断是通过自我报告和生化测量进行的。我们构建了结构方程模型量化了各变量的中介效应。 结果: 与受教育程度最低的男性相比，受过大学教育的男性患糖尿病风险较高(优势比OR:1.19, 95%可信区间(95%CI):1.12~1.27)，而受过大学教育的女性患糖尿病风险较低(OR:0.77, 95%CI:0.73~0.82)。肥胖在两性中均是最强的中介因素(中介比例:男性11.6%，女性23.9%)，肥胖与教育呈正相关(β[SE]0.0387[0.0037])，与女性中负相关(β[SE]‐0.0824[0.0030])。所有行为因素加在一起，可以解释12.4%的男性和33.3%的女性患糖尿病的额外风险。 结论: 在中国普通人群中，男性受教育程度与糖尿病之间存在正相关，而女性则为负相关。肥胖是糖尿病风险教育差异的主要中介因素，在女性中的中介作用更强。